Exploring film dynamics in the age of artificial intelligence: bibliometric visualization - Filosa Gita Sukmono; Nastiti Dyah Lestari; Helmy Muhammad (UPT Publikasi Ilmiah UNISBA, 2025)
This research aims to map trends, main themes, and scientific contributions in film studies in the era of artificial intelligence (AI) through a bibliometric approach. This study uses the PRISMA approach to compile a systematic literature selection, with Scopus data-based bibliometric analysis. Data were analyzed using VOSviewer to map thematic clusters and publication trends. Bibliometric analysis of 253 publications from the Scopus database revealed a significant increase in the trend of film research in the context of artificial intelligence since 2016, with a sharp spike in 2024. Eight main thematic clusters were successfully identified, including posthumanism, gender representation, machine learning-based film production, immersive cinema, deepfake ethics, AI literacy, and distribution through social media. The study also highlights the most influential scientific contributions, also examine the ethical, cultural, and social dimensions in depth. These findings suggest that cinema in the AI era is evolving as a discursive space that reflects technological transformation while opening up complex ethical and cultural debates. The results of this study show that artificial intelligence has significantly influenced the landscape of film research, both in terms of production and representation, as well as driving academic attention to ethical, cultural, and technological aspects of contemporary cinema.